There are too many kids with special educational needs - Taberner, Joanne E. (Frontiers in Education, 2023)
Over recent decades, special educational needs (SEN) policy and practice in the UK have been in flux as a succession of governments vacillates with competing social, political and economic agendas (Ekins, Savolainen & Engelbrecht, 2016; Norwich, 2014; Tomlinson, 2010). The simultaneous pursuit of educational standards, inclusion and equity has created a fragmented system, as well as cognitive and ethical dilemmas for schools (Baird et al., 2019; Lindsay, 2018; Shaw, Bernardes, Trethewey & Menzies, 2016; Webster & Blatchford, 2017). Moreover, a divisive ‘corporation’ (Deleuze & Guattari, 1987) and lucrative SEN industry have been established (Hayes & Ecclestone, 2008; Tomlinson, 2012), contributing to unsustainable growth of the SEN populace and political angst around SEN overidentification (Davies, 2019; Rayner, 2017; Squires, 2012). Indeed, the extant literature suggests that for every pupil correctly diagnosed with SEN, another is misdiagnosed, diverting resources from pupils with genuine needs (Baird et al., 2019; Davies, 2019; Galloway, 2019; Squires, Humphrey & Barlow, 2013; Timpson, 2019).